Stock Market Price movement prediction using RNN and Point-weight Sentiment - Uddin, S. M. Rageeb Noor; Naim, Jannatul Arafat; Pranjol, Mashuk Arefin; Ashrafi, Almas; Emon, Ibthasham Amin (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022